Impact of New-Onset Atrial Fibrillation on Mortality in Critically Ill Patients - Zhang HD; Ding L; Mi LJ; Zhang AK; Liu YD; Li XN; Yan XX; Shen YJ; Tang M (Clinical Epidemiology)
Hong-Da Zhang,* Lei Ding,* Li-Jie Mi, Ai-Kai Zhang, Yuan-Dong Liu, Xiang-Nan Li, Xin-Xin Yan, Yu-Jing Shen, Min Tang State Key Laboratory of Cardiovascular Disease, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences & Peking Union Medical College, Beijing, 100037, People’s Republic of China*These authors contributed equally to this workCorrespondence: Min Tang; Yu-Jing Shen, State Key Laboratory of Cardiovascular Disease, Fuwai Hospital, National Center for Cardiovascular Diseases, Chinese Academy of Medical Sciences & Peking Union Medical College, 167 Beilishi Road, Xicheng District, Beijing, 100037, People’s Republic of China, Email doctortangmin@yeah.net; shenyj0328@126.comBackground: Atrial fibrillation (AF) is the most prevalent cardiac arrhythmia in critically ill patients and significantly impacts mortality. This study sought to evaluate the impact of new-onset AF on mortality in a critically ill population.Methods: This study identified 48018 adult patients admitted to the ICU from the Medical Information Mart for Intensive Care (MIMIC)-IV database. Patients were categorized as no AF, pre-existing AF, or new-onset AF. We analyzed mortality at 3 months, 6 months, and 1 year.Results: Overall, 31,562 (65.73%) patients had no AF, 4877 (10.16%) had pre-existing AF, and 11,579 (24.11%) had new-onset AF. Median ages were 61.47 years (no AF), 76.12 years (pre-existing AF), and 75.26 years (new-onset AF). New-onset AF was associated with the highest mortality rates: 25.16% at 3 months, 29.23% at 6 months, and 34.04% at 1 year, compared to 17.94%, 22.55%, and 28.52% for pre-existing AF, and 14.54%, 17.25%, and 20.69% for no AF respectively (p < 0.001 for all). Multivariate Cox regression indicated that new-onset AF significantly increased the risk of 1-year mortality by 15.5% compared to no AF (HR: 1.155, 95% CI: 1.101– 1.212; p < 0.001) and by 23.9% compared to pre-existing AF (HR: 1.239, 95% CI: 1.164– 1.318; p < 0.001). Kaplan-Meier analysis confirmed lower survival probabilities for new-onset AF over one year compared to the other groups (p < 0.001).Conclusion: In patients with critical illness, new-onset AF is associated with an increased risk of mortality compared with pre-existing AF or no AF.Keywords: atrial fibrillation, mortality, intensive care unit